Electrochemical and photochemical CO2 reduction using diamond. (30th April 2021) - Yu, Siyu; Yang, Nianjun; Liu, Shetian; Jiang, Xin
Abstract: Catalysts are needed for electrochemical and photochemical reduction of CO2 into valuable chemicals. Diamond and its related materials have been regarded as a promising class of catalysts for CO2 reduction. With varied forms, structures, dopants, sp 2 /sp 3 ratios, surface functionalities, and the combination with different co-catalysts, a great diversity of diamond-based catalysts have been fabricated for CO2 reduction. This review summarizes state-of-art progress and achievements on the electrochemical CO2 reduction using different diamond and related electrodes, along with the selection of electrolytes and applied conditions. The applications of diamond nanoparticles and diamond related films for photochemical CO2 reduction are highlighted. The advanced strategies to further improve the catalytic activity of diamond towards CO2 reduction have been discussed and outlined. Graphical abstract: Image 1